Learned voluntary control of heart rate and rhythm in two subjects with premature ventricular contractions. Issue 2 (February 1977) - Pickering, T G; Miller, N E
Abstract : Two people with frequent premature ventricular contractions and bigeminal rhythm not associated with other signs of heart disease, learned to suppress the arrhythmia using a biofeedback technique. In both cases, physical exercise and atropine suppressed the arrhythmia, and in both the learned control was related to the development of tachycardia. In Case 1, it appeared to depend on something more than speeding alone, for sinus rhythm could be maintained during voluntary control at a lower heart rate than during physical manoeuvres such as exercise. In Case 2, the premature ventricular contractions could be induced by a sudden fall of heart rate, e.g. after a Valsalva manoeuvre, and could be suppressed by voluntary increase of heart rate by up to 40 beats/minute produced with little change in breathing or muscle activity.